2009
DOI: 10.1111/j.1524-4725.2008.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Injection Comfort of a New Category of Cohesive Hyaluronic Acid Filler With Preincorporated Lidocaine and a Hyaluronic Acid Filler Alone

Abstract: The smooth, cohesive HA gel with preincorporated lidocaine increased subject comfort during treatment and improved the injection experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 10 publications
1
33
0
1
Order By: Relevance
“…Thus, even if the charge interaction is one of the reasons for using the polyelectrolyte HA as a delivery vehicle [25], in our case, the large difference in molecular weight masked the influence of the charge interaction, confirming the major effects of molecular weight on drug release from a hydrogel [27]. The rapid in vitro release of lidocaine from the studied hydrogels is also consistent with the clinical observations, i.e., reduced pain during and after the administration of HA fillers containing lidocaine compared to fillers without lidocaine [28,29]. Notably, differences in the macrostructures of the three tested hydrogels did not affect drug release of both drugs.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, even if the charge interaction is one of the reasons for using the polyelectrolyte HA as a delivery vehicle [25], in our case, the large difference in molecular weight masked the influence of the charge interaction, confirming the major effects of molecular weight on drug release from a hydrogel [27]. The rapid in vitro release of lidocaine from the studied hydrogels is also consistent with the clinical observations, i.e., reduced pain during and after the administration of HA fillers containing lidocaine compared to fillers without lidocaine [28,29]. Notably, differences in the macrostructures of the three tested hydrogels did not affect drug release of both drugs.…”
Section: Discussionsupporting
confidence: 77%
“…Studies and the authors' experience have shown that the incorporation of lidocaine into dermal fillers significantly reduces pain and discomfort [62][63][64].…”
Section: Dermal Fillers With Lidocainementioning
confidence: 99%
“…Recent studies have shown that the use of pre-incorporated lidocaine in HA fillers greatly increases patient comfort during the procedure [6].…”
Section: 5 Million Reportedmentioning
confidence: 99%